2019
DOI: 10.1177/1535759719890337
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Dietary Therapy Controversies for Its Second Century

Abstract: As the ketogenic diet approaches 100 years of continuous use, we reflect on its successes and consider new avenues of research for the next century. One controversial question is regarding whether ketogenic dietary therapies could be successful first-line treatments for epilepsy. Second, is it possible to mimic the mechanisms of action of ketogenic dietary therapy with a drug (eg, a tablet formulation)? A third controversy worthy of future study involves its expanded usage in adults with refractory epilepsy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
(44 reference statements)
0
9
0
1
Order By: Relevance
“…The potential of using ketogenic supplements as a complemental strategy to carbohydrate restriction is discussed as ketogenic diet therapies are increasingly investigated in conditions beyond epilepsy (Kossoff and Cervenka, 2020 ), which include MCI/AD (Krikorian et al, 2012 ; Taylor et al, 2018 ; Brandt et al, 2019 ; Nagpal et al, 2019 ; Neth et al, 2020 ; Phillips et al, 2021 ). In a previous publication from the current clinical trial (Norgren et al, 2020b ), we demonstrated that supplementation with kMCT and time-restricted feeding regarding carbohydrates provide two—optionally additive—strategies to induce transient ketosis in older adults following their normal diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of using ketogenic supplements as a complemental strategy to carbohydrate restriction is discussed as ketogenic diet therapies are increasingly investigated in conditions beyond epilepsy (Kossoff and Cervenka, 2020 ), which include MCI/AD (Krikorian et al, 2012 ; Taylor et al, 2018 ; Brandt et al, 2019 ; Nagpal et al, 2019 ; Neth et al, 2020 ; Phillips et al, 2021 ). In a previous publication from the current clinical trial (Norgren et al, 2020b ), we demonstrated that supplementation with kMCT and time-restricted feeding regarding carbohydrates provide two—optionally additive—strategies to induce transient ketosis in older adults following their normal diet.…”
Section: Discussionmentioning
confidence: 99%
“…Ketogenic diets—which are based on strict carbohydrate restriction—have been used as a treatment for epilepsy since the 1920's (Kossoff and Cervenka, 2020 ), and are increasingly investigated in other neurological conditions, including Alzheimer's Disease (AD) (Stafstrom and Rho, 2012 ; Taylor et al, 2019 ). Induction of the metabolic state ketosis, characterized by increased circulating levels of the ketone body β-hydroxybutyrate (BHB), is a hallmark of ketogenic diets (Volek et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies have alerted of potential side effects (Cai et al, 2017), including an increase in serum lipidemia with concomitant increased risk of cardiovascular alterations (Zamani et al, 2016), higher risk of bone mass reduction (Simm et al, 2017), long-term alterations in the immune system (Goldberg et al, 2020), or increased probabilities for cardiac fibrosis (Xu et al, 2021). Because of these potential adverse effects, and the difficulty to adhere to the diet, different dietary formulations are being proposed to achieve a therapeutic effect with a more tolerable nutritional intervention (Dallérac et al, 2017;Kossoff and Cervenka, 2020). Furthermore, the anti-seizure efficacy in patients treated with ketogenic diets is not always replicated in experimental rodent models, which hampers research on the underlying molecular mechanisms (Holmes, 2008), This is probably due to biological differences in metabolic rates and in cellular responses to KBs between humans and rodents, as well as to the fact that ketosis is tightly controlled in humans to avoid dangerous situations, whereas mice and rats fed a ketogenic diet are allowed to eat ad libitum.…”
Section: Discussionmentioning
confidence: 99%
“…When conducted properly, a ketogenic diet is tolerated [ 27 ] and it can induce an increased number of patients achieving seizure freedom over time [ 14 , 28 ]. Then, a correct management of the ketogenic diet is also important to avoid side effects [ 16 , 17 , 19 ], controversies [ 29 ], and, in some cases, a phenomenon known as the rebound effect [ 30 ], which is characterised by a paradoxical seizure worsening [ 31 ]. Thus, the initiation and maintenance of the dietary treatment are the result of concomitant efforts of paediatric neurologists/epileptologists, dieticians, families and other patients’ caregivers [ 32 ].…”
Section: Discussionmentioning
confidence: 99%